2017
DOI: 10.1016/j.jenvrad.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and lateral distribution of fallout 137 Cs and soil properties along representative toposequences of central Rif, Morocco

Abstract: The purpose of this study is to understand and quantify the relationships between current Cs inventories and the soil properties and the physiographic characteristics. A total of 36 cores were taken in seven transects with different slopes, lithology and land use. The analysis focused on theCs mass activity as well as inventories and its relationship with soil properties as grain size and organic matter. The mass activity of Cs and the inventories varied between 3.6 and 63.7 Bq kg and between 521.7 and 3304.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…According to the literature, the soil organic matter contains chains of carbon atoms, containing polar and/or ionized surface functional groups, like OH – and COOH – , and generally, radionuclides strongly adsorbed to these functional groups and form stable complexes 19 . The strong correlation was not found between particle size and carbonate content of soil with 137 Cs radioactivity, which is consistent with the previous studies 4,15,35,36 . Concerning the moisture content, the positive correlation was obtained with 226 Ra activity concentrations with R 2 = 0.44 (see Supplementary Materials), which agreed with the study of 32 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…According to the literature, the soil organic matter contains chains of carbon atoms, containing polar and/or ionized surface functional groups, like OH – and COOH – , and generally, radionuclides strongly adsorbed to these functional groups and form stable complexes 19 . The strong correlation was not found between particle size and carbonate content of soil with 137 Cs radioactivity, which is consistent with the previous studies 4,15,35,36 . Concerning the moisture content, the positive correlation was obtained with 226 Ra activity concentrations with R 2 = 0.44 (see Supplementary Materials), which agreed with the study of 32 .…”
Section: Resultssupporting
confidence: 92%
“…Figure 1 shows that the organic matter is very low for all soil samples mainly due to low vegetation cover; it varies from 0.08% to 0.68%. Because of the high cationic exchange capacity of the organic matter, the results of low organic matter may lead to assumption that adsorption in soil samples may be controlled mainly by an ion exchange mechanism with the clay minerals 15 . Organic matter is of great importance because it tends to form soluble or insoluble complexes with radionuclides, which may then transport throughout the profile or retain within the soil 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the 137 Cs technique have confirmed its potential over the medium term (∼50 years) for estimating soil redistribution rates (Alewell, Meusburger, Juretzko, Mabit, & Ketterer, ; Gaspar, Navas, Walling, Machín, & Gómez Arozamena, ; Mabit, Bernard, Makhlouf, & Laverdière, ; Navas & Walling, ; Sadiki, Faleh, Navas, & Bouhlassa, ) and for validating spatially distributed catchment erosion and sediment yield models (Collins, Walling, Sichingabula, & Leeks, ; Du & Walling, ; Mabit, Bernard, & Laverdiere, ; Mesrar et al, ; Quijano, Beguería, Gaspar, & Navas, ).…”
Section: Introductionmentioning
confidence: 97%
“…Higher the content of alumina in the clay, better is the refractoriness of the clay [41]. The content of alumina inversely affects the mechanical strength of ceramics [42].…”
Section: X-ray Fluorescencementioning
confidence: 99%